2018
DOI: 10.3390/systems6040036
|View full text |Cite
|
Sign up to set email alerts
|

Communities of Practice Approach for Knowledge Management Systems

Abstract: In this digital world, organisations are facing global competition as well as manpower pressures leading towards the knowledge economy, which heavily impacts on their local and international businesses. The trend is to foster collaboration and knowledge sharing to cope with these problems. With the advancement of technologies and social engineering that can connect people in the virtual world across time and distance, several organisations are embarking on knowledge management (KM) systems, implementing a comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In particular, by exploring the extent to which its content aligns with the knowledge management theory, it offers an opportunity to examine whether or not it operates as an established knowledge management system. This study sought to answer the following question: What types of information and advice were shared on Twitter using #FOAMed during the COVID- 19…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, by exploring the extent to which its content aligns with the knowledge management theory, it offers an opportunity to examine whether or not it operates as an established knowledge management system. This study sought to answer the following question: What types of information and advice were shared on Twitter using #FOAMed during the COVID- 19…”
Section: Original Researchmentioning
confidence: 99%
“…15 Social media research has identified the benefits of using knowledge management models to understand how information is shared and curated. [16][17][18] Karl Wiig is widely considered a pioneer in this field, and his knowledge management cycle framework 19 on December 27, 2020 by guest. Protected by copyright.…”
Section: Introductionmentioning
confidence: 99%
“…Social connectivity (S) can be leveraged to allow team-based support or learning through training. Users can collaborate to complete exercises during training to practice applying their newly acquired knowledge and skills, and leaderboards can be used to track each team's progress [109]. For example, creating a simulated system issue that teams have to research and solve can be introduced during training, and the teams with the most innovative and efficient solution recognized.…”
Section: Gamification In User Training Of Enterprise Systemsmentioning
confidence: 99%
“…Organizations have to create conducive environments for employees to voluntarily participate in their pursuit for knowledge sharing and organizational learning, and also to cultivate a corporate culture in establishing social structures for knowledge sharing through quality interactions and meaningful discussions [52].…”
Section: Intagible Assets Capabilities Knowledge and Business-it Smentioning
confidence: 99%
“…A social network is a set of interconnected people who directly or indirectly interact and influence each other [52]. A social network is a pattern of ties linking a defined set of persons or social actors [54].…”
Section: Social Networkmentioning
confidence: 99%